Physicochemical and oxidative stability of indigenous traditional tengkawang butter as potential cocoa butter equivalent (CBE). Issue 1 (31st December 2022) - Darmawan, Muhammad Arif; Ramadhan, Muhammad Yusuf Arya; Curie, Catia Angli; Sahlan, Muhammad; Utami, Tania Surya; Abd-Aziz, Suraini; Cognet, Patrick; Aroua, Mohamed Kheireddine; Gozan, Misri
ABSTRACT: This study identified the quality, physicochemical properties, and oxidation stability of tengkawang butter (TB) from indigenous plants in various areas of Kalimantan, Indonesia. The fatty acid profile was dominated by palmitic acid, stearic acid, and oleic acid. Acidity ranged from 6.88 to 15.94%, while the peroxide number was 0.41 and 8.27 meq O2 /kg. TB had a melting point of 36–37°C. The solid fat content (SFC) varied from 0.03 to 3%. The Oxidation Stability Index (OSI22 ) was more than 10, 000 h. The composition and properties show the potential of TB to become a cocoa butter equivalent (CBE).